Tax Revenue and Economic Growth: A Study of Nigeria and Ghana - Francis Chinedu Egbunike; Ochuko Benedict Emudainohwo; Ardi Gunardi (Signifikan: Jurnal Ilmu Ekonomi, 2018)
Tax revenue is frequently considered as an alternative form of sustainable financing within a stable and predictable fiscal environment to promote growth and enable governments to finance their social and infrastructural needs. The objective of the study is to examine the effect of tax revenue on economic growth of Nigeria and Ghana. The study used multiple regressions as tools of analysis. The study finds a positive impact of tax revenue on the gross domestic product of Nigeria and Ghana confirming prior studies. The study recommended among others that adequate measure to ensure that revenue generated from the tax is effectively utilized to develop and grow the economy.DOI: 10.15408/sjie.v7i2.7341